Comparison of Different Nanosuspensions as Potential Ophthalmic Delivery Systems for Ketotifen Fumarate - Saieede Soltani; Parvin Zakeri-Milani; Mohammad Barzegar-Jalali; Mitra Jelvehgari (Advanced Pharmaceutical Bulletin, 2016)
Purpose: The objective of this study was to develop, characterize, and comparatively investigate the ketotifen fumarate (KF) nanosuspensions (NSS) to enhance the permeability of KF.